Is innervation an early target in autoimmune diabetes? - Saravia, Flavia Eugenia (2003)
In the non-obese diabetic (NOD) mouse, a spontaneous model of type 1 diabetes (T1D), recent evidence suggests that Schwann cells (Scs) and neurons surrounding insulin-producing β cells of the islets of Langerhans are destroyed before β cells. During normal perinatal development, macrophages (MΦ) are involved in phagocytosis of apoptotic neurons. Pertinently, MΦ are already present at birth in NOD pancreata. Their possible abnormal control of nerve phagocytosis, together with transient β-cell hyperactivity and lymphocyte anomalies, might conjointly participate in T1D pathogenesis.